KETERLAMBATAN PENYELESAIAN SKRIPSI MAHASISWA ANGKATAN 2012 (STUDI KASUS DI JURUSAN EKONOMI PEMBANGUNAN FAKULTAS EKONOMI UNIVERSITAS NEGERI MALANG) - Evi Nur Aslinawati; Sri Umi Mintarti (Jurnal Pendidikan Ekonomi, 2017)
This study departs from the problem of the number of students who havedelayed graduation because they cannot complete the thesis on time. Forthat, it is necessary to do research to determine the cause of thesis by thestudents. The type of research conducted is qualitative descriptive, with thelocation of research in Economic Development Department Faculty ofEconomics, State University of Malang. Technical data is done through.Data analysis is done in data processing, presentation, and data verification.The result of research indicates the existence of internal factor causingdelays of completion of thesis of health factor, weakness of motivation,interest, level of intelligence (IQ, SQ, AQ, and EQ), difficulty indetermining research topic, accuracy in collecting data and analyzingresearch data, Scientific papers, work, active organization, and low ability ofstudents in time management. While external factors include the motivationof the family, interest in reference, the relationship between lecturers andstudents, and the environment of peers.DOI: https://dx.doi.org/10.17977/UM014v10i12017p026